2020
DOI: 10.1186/s12879-020-05203-3
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypic and molecular characteristics of antimicrobial resistance of Salmonella enterica subsp. enterica serovar Typhimurium in Henan Province, China

Abstract: Background: Salmonella enterica subsp. enterica serovar Typhimurium infections continue to be a significant public health threat worldwide. The aim of this study was to investigate antibiotic resistance among 147 S. Typhimurium isolates collected from patients in Henan, China from 2006 to 2015. Methods: 147 S. Typhimurium isolates were collected from March 2006 to November 2015 in Henan Province, China. Antimicrobial susceptibility testing was performed, and the resistant genes of ciprofloxacin, cephalosporins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 51 publications
4
18
1
Order By: Relevance
“…Kentucky, and S . Typhimurium strains but not in other serotypes ( 7 , 25 27 ). Instead, PMQR genes, often in the form of multiple PMQR genes located in the chromosome and plasmids, now are commonly detectable in ciprofloxacin-resistant Salmonella strains of various serotypes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Kentucky, and S . Typhimurium strains but not in other serotypes ( 7 , 25 27 ). Instead, PMQR genes, often in the form of multiple PMQR genes located in the chromosome and plasmids, now are commonly detectable in ciprofloxacin-resistant Salmonella strains of various serotypes.…”
Section: Discussionmentioning
confidence: 88%
“…Currently, target gene mutations, in particular single mutation in the gyrA gene, may be detected in S. Typhimurium but is rarely seen in other serotypes of Salmonella. Double mutations in gyrA and single mutation in parC that mediated high-level resistance were seen only in S. Indiana, S. Kentucky, and S. Typhimurium strains but not in other serotypes (7,(25)(26)(27). Instead, PMQR genes, often in the form of multiple PMQR genes located in the chromosome and plasmids, now are commonly detectable in ciprofloxacinresistant Salmonella strains of various serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…ST19 and ST34 prevalence in Salmonella 4,[5],12:i:- has significantly increased in Canada, and some of these STs demonstrate quinolone resistance [ 30 ]. It has been reported that ST19 is significantly associated with ciprofloxacin resistance in China [ 31 ] and that ST34 is linked to the nalidixic acid resistance in Africa [ 32 ]. Salmonella Agona ST13 was the most prevalent serovar isolated from chicken meat in Sri Lanka [ 33 ], and a Salmonella Agona strain isolated from chicken meat in China possessed a T57S substitution in ParC and carried qnrS [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although S. Enteritidis usually causes predominantly self-limiting enteric disease, some severe clinical illnesses require antibiotics. In particular, fluoroquinolones and extended-spectrum cephalosporins, such as cefotaxime and ceftazidime, are considered first-line clinical drugs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%